A practical guide to dissertation and thesis writing - Felix, Mark Stephan (Cambridge Scholars Publishing, 2019)
"This book provides a step-by-step guide to writing the different chapters of a PhD dissertation, which will benefit aspiring, beginner and mid-track PhD students and candidates in the Social Sciences. Based on the authors'combined experience of working with both Masters and PhD students through the dissertation writing process, it offers helpful writing guidelines, from the conceptualization and problematization of the dissertation through to the literature review, methodological issues, writing up results and, finally, to the discussion, conclusions and abstract writing process. With chapters dedicated to offering guidelines, suggestions and pitfalls to watch out for, this book will assist PhD students and candidates in the fields of the various Social Sciences with exercises and pointers on successfully navigating the writing of a PhD dissertation. It takes the PhD student in the Social Sciences through the maze of writing a dissertation, and provides a step-by-step train of thought throughout the entire writing process."--Publisher.